2004
DOI: 10.1007/s00425-003-1120-6
|View full text |Cite
|
Sign up to set email alerts
|

A single recessive mutation in the proteolytic machinery of Arabidopsis chloroplasts impairs photoprotection and photosynthesis upon cold stress

Abstract: Intracellular proteases, together with molecular chaperones, are components of the cellular protein quality control system. Although the identity of chloroplast proteases has been revealed in recent years, little is known about their regulation. As a first step towards identifying unknown functional or regulatory components of the chloroplast proteolytic machinery, a genetic screen was devised with the aim of generating Arabidopsis thaliana (L.) Heynh. mutants impaired in chloroplast protein degradation. A str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is also possible that coldinduced proteases degrade cellular proteins that have been denatured by low temperature. In support of this notion, Levy et al (2004) identified a mutant in the chloroplast proteolytic machinery which exhibited impaired photoprotection and photosynthesis upon cold stress.…”
Section: Regulatory Proteinsmentioning
confidence: 84%
“…It is also possible that coldinduced proteases degrade cellular proteins that have been denatured by low temperature. In support of this notion, Levy et al (2004) identified a mutant in the chloroplast proteolytic machinery which exhibited impaired photoprotection and photosynthesis upon cold stress.…”
Section: Regulatory Proteinsmentioning
confidence: 84%
“…Chloroplast, a photosynthesis site in a plant, is one of the first organelles affected by cold stress and it extremely sensitive to cold stress [10,11]. Chloroplast proteolytic machinery is involved in repairing damage incurred to the photosynthetic machinery upon exposure to cold stress [12]. The cold-tolerant ecotype of Valonia utricularis is able to cope with the applied low temperature stress by down-regulating the PSII RCs, whereas the cold-sensitive ecotype has a generally lower capacity for dynamic photoinhibition and sustains photodamage [13].…”
Section: Introductionmentioning
confidence: 99%